The effects of job rotation towards job performance: a research on employees in the Department of Immigration Malaysia (Johor) / Nur Izzati Idris and Siti Shariya Mohd Salleh - Idris, Nur Izzati; Mohd Salleh, Siti Shariya (Faculty of Business and Management, 2015)
The purpose of this study is to investigate the relationship between effects of job rotation and job performance. A sample size of 113 participants was generated from Management Division by using random sampling among staffs in of Immigration Department Johor. Data analyze by using Statistical Package for Social Sciences (SPSS) and Cronbach’s Alpha test was use to check reliability coefficient, Pearson Correlation to test relationship between effect of job rotation and job performance, Multiple Regression to rank the most effect of job rotation toward job performance. The result shows that the effects of job rotation are positively influencing job performance and correct job or position is the most factor of job rotation towards job performance. The finding shows that the research model is significant and acceptable hence, the three independent variables are strongly influencing dependent variable. The implication is short term of period was use to get the result of research so it suggested that for further researcher should use long-term of time to obtain better result for example within one years of period rather than three month of period.